A study of the ‘imagetexts’ of the Daoist visual culture, signifying the tripartite realms of Heaven, Human, Earth - Han, Yuhui (2014)
This is a study of Imagetexts in Daoism visual culture, signifying the structure of the cosmos in a corresponding relationship with one other. By structure of the cosmos, I will be looking at the tripartite realms of existence, namely Heaven, Earth and Human as the three forces that are unified in the Dao.